Criminal participation in the legal economy during a health crisis: A screening of the Italian economy during 2020 and 2021 - Giovanni Nicolazzo (Journal of Economic Criminology)
This paper investigates patterns of suspicious participation into the legal economy during the coronavirus pandemic (2020-2021), with a focus on the Italian context. Moving beyond traditional reliance on law enforcement or judicial data, it applies a proxy-based methodology to identify red-flags in company ownership structures that may signal potential criminal influence. By comparing incorporations and ownership changes before and during the pandemic, the study highlights shifts in the frequency and distribution of selected suspicious features. As an initial academic application of screening techniques, the study offers a practical framework for monitoring emerging trends in the criminal involvement within the legal economy and lays the groundwork for further methodological refinement in this field.